2018
DOI: 10.12913/22998624/85704
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of the Tool Surface Texture on Friction and the Surface Layers Properties of Formed Component

Abstract: The morphological texturing of forming tool surfaces has a high potential to reduce friction and tool wear and also has an impact on the surface layers properties of formed material. In order to understand the effect of different types of tool textures, produced by nanosecond fibre laser, on the tribological conditions at the interface tool-formed material and on the integrity of formed part surface layers, the series of experimental investigations have been carried out. The coefficient of friction for differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Micro-texturing the surface of deep drawing tools can significantly reduce friction in certain areas of the drawpiece [198]. Šugárová et al [206] indicated that a surface density of depressions in the area of 13% is preferred to reduce the value of the COF. An areal density of pits above 20% usually causes an increase in the COF and wear rate [198].…”
Section: Structured and Textured Tool Surfacesmentioning
confidence: 99%
“…Micro-texturing the surface of deep drawing tools can significantly reduce friction in certain areas of the drawpiece [198]. Šugárová et al [206] indicated that a surface density of depressions in the area of 13% is preferred to reduce the value of the COF. An areal density of pits above 20% usually causes an increase in the COF and wear rate [198].…”
Section: Structured and Textured Tool Surfacesmentioning
confidence: 99%
“…The formability of steel plates and the shape of the final parts made from them depend on factors such as the material (its mechanical properties and surface microgeometry) [1,2]; the forming die geometry (die clearance, radii of the punch and die) and microgeometry (roughness of contact surfaces) [3][4][5]; the technological parameters (temperature, strain rate, blank holding forces, contact pressure, etc.) [6][7][8]; the properties of the tool's material (hardness, chemical composition, structure) [9]; and the type and amount of lubricant used [10].…”
Section: Introductionmentioning
confidence: 99%
“…The ablation with femtosecond‐lasers generates topographies characterized by periodic nano‐structured ripples that were recently used to modify the surface properties for an increasing number of applications . In particular, LIPSS have been successfully used to modify the wettability of steel surfaces , improve their tribological behavior , and increase hardness and wear resistance .…”
Section: Introductionmentioning
confidence: 99%